Sistem Pendukung Keputusan Klinis Dalam Keperawatan - Muminah Muminah; Rr. Tutik Sri Haryati (Jurnal Keperawatan Muhammadiyah, 2022)
Introduction: Clinical decision making in nursing requires the support of accurate data and a well-constructed system. But currently clinical decision making in nursing has not been widely not even supported by clinical decision support systems in both hospitals and other health services. Objective: know the support system of clinical decisions that can be applied in clinical decision making by nurses in health services, especially hospitals. Method: Systematic searches are performed in proquest and Scopus databases with the keywords Clinical decision support system and Nursing. Inclusion criteria are articles published in the last 5 years of 2017 to 2021, full text, discussing the use of clinical decision support systems by nurses, using all research methods both qualitative, quantitative, mixed methods, cohorts and surveys and English articles. Results: Obtained six research articles that fit the criteria of inclusion. Consists of studies of the utilization of clinical decision support systems in the emergency department triage, accuracy in determining nursing diagnoses, monitoring patient conditions, nurse experience in receiving patient condition reports over the phone. Discussion: The Clinical Decision Support System is very useful for improving the accuracy of triage in the emergency department. In addition, it also improves the professionalism of nursing care including drug management.